Correction: Highly-efficient semi-transparent organic solar cells utilising non-fullerene acceptors with optimised multilayer MoO3/Ag/MoO3 electrodes. (10th April 2019) - Sun, Guangjun; Shahid, Munazza; Fei, Zhuping; Xu, Shenda; Eisner, Flurin D.; Anthopoulos, Thomas D.; McLachlan, Martyn A.; Heeney, Martin
Abstract : Correction for 'Highly-efficient semi-transparent organic solar cells utilising non-fullerene acceptors with optimised multilayer MoO3 /Ag/MoO3 electrodes' by Guangjun Sun et al., Mater. Chem. Front., 2019, 3, 450–455.